2018
DOI: 10.4274/jpr.08870
|View full text |Cite
|
Sign up to set email alerts
|

Serum Antioxidative Enzymes Levels and Oxidative Stress Products in Children and Adolescents with Type I Diabetes Mellitus

Abstract: Type I diabetes mellitus (TIDM) is an oxidative stress condition in addition to being a chronic metabolic disease. In this study, our aim is to investigate the activity of antioxidative enzymes and the products of oxidative stress in children and adolescents with TIDM and compare the findings with those in healthy control subjects. Materials and Methods: The study enrolled 41 children and adolescents with TIDM (mean age 11.4±3.3 years; 21 female, 20 male) and 25 healthy subjects (mean age 11.3±3.1 years; 8 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…Malondialdehyde (MDA) and protein carbonyl (PC) are commonly used as biomarkers in plasma. [ 12 13 14 15 16 ] Some studies reported that plasma levels of MDA or PC in the T1DM group were higher than in the control group,[ 12 13 14 ] while others found no differences between the groups. [ 15 16 ] Total oxidant status (TOS), developed in 2005,[ 17 ] has been used in studies of cancer patients,[ 18 ] periodontal disease,[ 19 ] and T2DM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malondialdehyde (MDA) and protein carbonyl (PC) are commonly used as biomarkers in plasma. [ 12 13 14 15 16 ] Some studies reported that plasma levels of MDA or PC in the T1DM group were higher than in the control group,[ 12 13 14 ] while others found no differences between the groups. [ 15 16 ] Total oxidant status (TOS), developed in 2005,[ 17 ] has been used in studies of cancer patients,[ 18 ] periodontal disease,[ 19 ] and T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 13 14 15 16 ] Some studies reported that plasma levels of MDA or PC in the T1DM group were higher than in the control group,[ 12 13 14 ] while others found no differences between the groups. [ 15 16 ] Total oxidant status (TOS), developed in 2005,[ 17 ] has been used in studies of cancer patients,[ 18 ] periodontal disease,[ 19 ] and T2DM. [ 20 ] In T1DM, Aral et al [ 21 ] found that salivary TOS was higher in patients with T1DM at diagnosis compared with a healthy group; however, no significant difference was recorded between patients with T1DM and controls with gingivitis.…”
Section: Introductionmentioning
confidence: 99%